Linguistic Impoliteness and Power Relations In AlRawabi School For Girls: An Analysis Based On Culpeper’s Theory: Al-Waqahah al-Lughawiyyah wa ‘Alaqat al-Quwwah fi Madrasat al-Rawabi lil-Banat: Tahlil fi Daw’i Nazariyyat Culpeper - Alifa Maisya Ratunisa (An-Nahdah Al-'Arabiyah, 2026)
This study examines linguistic impoliteness strategies in the Netflix series AlRawabi School for Girls based on Jonathan Culpeper's impoliteness theory using a descriptive qualitative approach within a pragmatic framework. Data were collected from verbal utterances across all six episodes using official Netflix subtitles and resulted in 27 impolite utterances identified for analysis. Among the identified strategies, positive impoliteness was the most dominant strategy with 12 utterances (44%), followed by bald on record impoliteness with 10 utterances (37%), negative impoliteness with 3 utterances (11%), sarcasm or mock politeness and withhold politeness with 1 utterance each (4%). These findings demonstrate that linguistic impoliteness functions not only as an emotional expression but also as a social practice in which characters establish dominance, negotiate power relations, and reinforce social hierarchies. By extending beyond the identification of impoliteness strategies, this study contributes to pragmatic studies of impoliteness by providing a contextual understanding of how linguistic impoliteness operates within an Arab adolescent school setting.   تهدف هذه الدراسة إلى استراتيجيات الوقاحة اللغوية في مسلسل "مدرسة الروابي للبنات" على منصة Netflix ، بناءً على نظرية جوناثان كولبيبر حول الوقاحة اللغوية، باستخدام نهج وصفي نوعي في إطار براغماتي.  تم جمع البيانات من الحوارات الشفهية في جميع حلقات المسلسل الست باستخدام الترجمة الرسمية لنتفليكس، وأسفر عن تحديد 27 عبارة الوقاحة اللغوية للتحليل. من بين جميع الاستراتيجيات التي تم تحديدها، كانت الوقاحة الإيجابية هي الاستراتيجية الأكثر شيوعًا بواقع 12 عبارة (44%)، تليها الوقاحة المباشرة بواقع 10 عبارات (37%)، ثم الوقاحة السلبية بواقع 3 عبارات (11%)، وأخيرًا السخرية أو الأدب الزائف، و حجب الأدب بواقع عبارة واحدة لكل منهما (4%). تُظهر هذه النتائج أن الوقاحة اللغوية لا تقتصر على كونها تعبيرًا عاطفيًا فحسب، بل هي أيضًا ممارسة اجتماعية تُرسّخ من خلالها الشخصيات هيمنتها، وتُدير علاقات القوة، وتُعزز التسلسل الهرمي الاجتماعي. من خلال تجاوز مجرد تحديد استراتيجيات الوقاحة اللغوية، تساهم هذه الدراسة في الدراسات البراغماتية للوقاحة اللغوية من خلال توفير فهم سياقي لكيفية عمل الوقاحة اللغوية داخل بيئة مدرسية للمراهقين العرب.   Penelitian ini mengkaji strategi ketidaksantunan berbahasa dalam serial Netflix AlRawabi School for Girls berdasarkan teori impoliteness Jonathan Culpeper dengan menggunakan pendekatan kualitatif deskriptif dalam kerangka analisis pragmatik. Data dikumpulkan dari ucapan verbal di enam episode menggunakan subtitle resmi Netflix dan menghasilkan sebanyak 27 tuturan tidak sopan diidentifikasi untuk dianalisis. Dari semua strategi yang diidenfitifikasi, positive impoliteness adalah strategi paling dominan dengan 12 tuturan (44%), diikuti bald on record impoliteness dengan 10 tuturan (37%), negative impoliteness 3 tuturan (11%), sarcasm or mock politeness dan withhold politeness masing-masing 1 tuturan (4%). Temuan ini menunjukkan bahwa ketidaksantunan berbahasa tidak hanya berfungsi sebagai ekspresi emosional tetapi juga sebagai praktik sosial di mana tokoh-tokoh membangun dominasi, menegosiasikan hubungan kekuasaan, dan memperkuat hierarki sosial. Dengan melampaui identifikasi strategi ketidaksopanan, penelitian ini berkontribusi pada studi pragmatik tentang ketidaksantunan dengan memberikan pemahaman kontekstual tentang bagaimana ketidaksopanan linguistik beroperasi dalam lingkungan sekolah remaja Arab.